Delayed diagnosis of Brugada syndrome in a patient with aborted sudden cardiac death and initial negative flecainide challenge. Issue 12 (31st October 2017) - Chauveau, Samuel; Le Vavasseur, Olivier; Chevalier, Philippe
Key Clinical Message: A negative flecainide challenge does not rule out Brugada syndrome even in the presence of nonfatal cardiac arrest as the first manifestation of the disease. This should prompt clinicians to ensure long‐term ECG follow‐up and consider repeating a drug test with another sodium channel blocker. Abstract : A negative flecainide challenge does not rule out Brugada syndrome even in the presence of nonfatal cardiac arrest as the first manifestation of the disease. This should prompt clinicians to ensure long‐term ECG follow‐up and consider repeating a drug test with another sodium channel blocker.